2006
DOI: 10.1111/j.1365-2516.2006.01259.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and genetic therapies for haemophilia

Abstract: Summary. Haemophilia continues to be a prime target for a variety of gene and cell-based therapies. Pre-clinical successes in both mouse and dog models of the disease have been documented with a variety of approaches over the past decade, and there have now been six small clinical trials of gene transfer in haemophilia. To date, the only significant adverse events documented in these trials have been related to host immune responses, indicating that immunologic barriers continue to represent the major obstacle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 34 publications
(31 reference statements)
0
42
0
1
Order By: Relevance
“…As a result, viral vectors have been the predominant system for in vivo transgene delivery and use in human clinical hemophilia trials (34). However, a number of concerns have emerged regarding their use, including antigenicity, mutagenicity, cost, and defined tropisms (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, viral vectors have been the predominant system for in vivo transgene delivery and use in human clinical hemophilia trials (34). However, a number of concerns have emerged regarding their use, including antigenicity, mutagenicity, cost, and defined tropisms (35).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mice used in this study came from the same colony as those reported previously (54). Although the problem of inhibitor formation was overcome by neonatal tolerization of the mice with recombinant huFVIII protein, it continues to be a major obstacle in FVIII gene replacement strategies in animal models (34), requiring additional approaches for tolerization (56,57). In fact, in a recent adeno-associated virus study, longterm persistent FVIII expression in adult dogs was achieved in the absence of inhibitor formation (58).…”
Section: Figurementioning
confidence: 99%
“…Gene therapy or cell-based approaches have the potential to provide a life-long, cost-effective cure for hemophilia A. 2 A number of clinical trials for hemophilia A gene therapy have been performed. 3,4 So far, limited clinical efficacy of gene delivery approaches has been observed.…”
Section: Introductionmentioning
confidence: 99%
“…rAAVs have proven to be efficient in preclinical studies in animal models (16,28), and results from clinical trials are promising (7,47).…”
mentioning
confidence: 99%